Chemical Composition and Nutritive Value of Oplismenus compositus (Linn.) P. Beauv - Pandey, Seema; Drami, K. S. (Indian Forester, 2002)
Samples of Oplismenus compositus collected from July to November were analysed for the detection and determination of protein, amino acids, sugars, fat and minerals. In early stages of growth, it was found to accumulate more fat, amino acids and minerals. Hence it is of maximum utility if used during that period. However, it may be used as fresh fodder up to November as well as harvested and stored for dry season.